1984
DOI: 10.1007/bf01952340
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of basaltic xenoliths in andesitic to dacitic host lavas from Martinique (lesser antilles): Evidence for magma mixing

Abstract: Some recent calc-alkaline andesites and dacites from southern and central Martinique contain basic xenoliths belonging to two main petrographic types: -The most frequent one has a hyalodoleritic texture (~>) with hornblende + plagioclase + Fe-Ti oxides, set in an abundant glassy and vacuolar groundmass.-The other one exhibits a typical porphyritic basaltic texture (~( B type >>) and mineralogy (oli~_ne + plagioclase + orthopyroxene + clinopyroxene + Fe-Ti oxides and scarce, or absent hornblende).Gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…Under these conditions, amphibole is the most abundant phase, exceeding plagioclase in the mineral assemblage (Table 7; see also Holloway and Burnham [1972]). This reproduces one important aspect of mafic enclaves and gabbroic cumulates from the Lesser Antilles arc, namely, the high modal abundance of amphibole [ Arculus and Wills , 1980; Coulon et al , 1984; Fichaut et al , 1989b; Gourgaud et al , 1989]. It has been suggested that fractionation of a Plag + Amph assemblage is responsible for the chemical trends seen in Lesser Antilles lavas [ Arculus and Wills , 1980].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Under these conditions, amphibole is the most abundant phase, exceeding plagioclase in the mineral assemblage (Table 7; see also Holloway and Burnham [1972]). This reproduces one important aspect of mafic enclaves and gabbroic cumulates from the Lesser Antilles arc, namely, the high modal abundance of amphibole [ Arculus and Wills , 1980; Coulon et al , 1984; Fichaut et al , 1989b; Gourgaud et al , 1989]. It has been suggested that fractionation of a Plag + Amph assemblage is responsible for the chemical trends seen in Lesser Antilles lavas [ Arculus and Wills , 1980].…”
Section: Discussionmentioning
confidence: 61%
“…Information on the mafic part of the chamber comes from mafic enclaves erupted during stage 3 and from mafic lavas (ash‐and‐scoria flows) and gabbroic cumulates from stage 2. Mafic enclaves have phenocryst compositions differing relatively little from phenocrysts in andesites (Figures 4–6, 12, and 13), probably because they were hybridized [e.g., Coulon et al , 1984; Bacon , 1986; Clynne , 1999]. Mafic lavas from stage 2 also carry a minor andesite “component” [ Bourdier et al , 1985], but these, together with gabbroic cumulates, appear to preserve phenocryst and glass compositions representative of the mafic part of the system (Tables 2–5 and see below).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large acicular skeletal or microlitic crystals are observable within C and C±S stuctures, either coated by glass or included within doleritic minerals. This particular texture, which resemble the ªhyalodoleriticº texture defined by Lacroix (1904; see also Coulon et al 1984), has been identified herein as the GDAC texture (glassy or doleritic texture with large acicular crystals). Self et al (1996Self et al ( , 1997 and Kent et al (1998) have also described cylinder sheets and cylinders, respectively, in thicker ( 6 15 m) inflated pahoehoe lava flows.…”
Section: Sg Sgmentioning
confidence: 98%
“…Most of the mafic xenoliths in volcanic rocks from island arc systems fall into one of three categories: cognate xenoliths that are indicative of magma mixing [e.g. 6,7], plutonic blocks derived from middle to lower crustal sources [e.g. 8,9], or cumulate rocks formed by crystallization and precipitation in magma reservoirs [e.g.…”
Section: Introductionmentioning
confidence: 99%